Customer Satisfaction And Product Quality - Maryoso, Slamet; Hamzah, Ramadhani; Astri, Fitriyah; Yanto Rukmana, Arief; Apramilda, Riesna (Yayasan Pendidikan Belajar Berdikari, 2023)
This study project aims to understand (1) the effect of product quality on customer satisfaction in Sukabumi Mixue Beverage Product consumers. (2) the impact of pricing on customer happiness among Sukabumi Mixue Beverage Product customers (3) the impact of product quality on customer loyalty among Sukabumi Mixue Beverage Product customers (4) the impact of price on customer loyalty (5) the impact of Customer Satisfaction on Customer Loyalty in Sukabumi Mixue Beverage Product Users (6) The impact of Product Quality on Customer Loyalty via Customer Satisfaction in Sukabumi Mixue Beverage Product Consumers (7) The effect of price on customer loyalty as measured by customer satisfaction in Sukabumi Mixue Beverage Product consumers. This research endeavor employs both an associative and quantitative approach. This research activity's demographic consists of Mixue beverage drinkers in the Sukabumi area. While the sample is made up of Sukabumi residents who have purchased and consumed Mixue beverage goods more than once and are over the age of 15, the total number of respondents is 88. The route analysis technique was utilized to analyze the data. Product Quality (X1) has a positive and significant effect on Customer Satisfaction (Z), Price (X2) has a positive and significant effect on Customer Satisfaction (Z), and Customer Satisfaction (Z) has a positive and significant effect on Customer Loyalty (Y). Product Quality (X1) also has a positive and significant effect on Customer Loyalty (Y) through Customer Satisfaction (Z), and Price (X2) has a positive and significant effect on Customer Loyalty (Y) through Customer Satisfaction (Z). These findings are the outcome of the analysis of this research activity